Improving the Quantity and Quality of Biogas Production in Tehran Anaerobic Digestion Power Plant by Application of Materials Recirculation Technique - Naghavi, Reza; Abdoli, Mohammad Ali; Karbasi, Abdolreza; Adl, Mehrdad (International Journal of Renewable Energy Development, 2020)
Tehran anaerobic digestion power plant has been built on the eastern margin of the urban district by the purpose of processing the organic fraction of municipal solid waste. One of the most suitable methods for the treatment of organic matter is the use of anaerobic digestion (AD) process, which in addition to significant reduction of organic solid wastes, will produce valuable energy. Contributing to maintain the environment, improve urban health, saving on fossil fuels and producing rich fertilizer for agricultural use are important advantages of anaerobic digestion. The plant has been set up in 2014 with a nominal acceptance capacity of 300 tons of organic solid wastes per day and the nominal power generation of 2000 kWe. This system has been faced with considerable challenges in terms of quantity and quality of biogas during operation. The high concentration of hydrogen sulfide (H2S) in produced biogas and the lack of appropriate technologies in the plant for biogas refining are critical for the biogas generator engine deployed in the complex. The purpose of this article is to investigate the factors affecting the quality and quantity of Tehran's AD plant biogas using various H2S reduction approaches and selection of appropriate implementing technologies. The results showed that the recirculation of the digester slurry increased the methane content by more than 30% and reduced H2S by more than 98%.